2021
DOI: 10.2147/jir.s326416
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shaoyao Gancao Decoction on Sphincter of Oddi Dysfunction in Hypercholesterolemic Rabbits via Protecting the Enteric Nervous System–Interstitial Cells of Cajal–Smooth Muscle Cells Network

Abstract: Objective This study observes the morphological changes in the enteric nervous system (ENS) – interstitial cells of Cajal (ICC) – smooth muscle cells (SMC) network in sphincter of Oddi dysfunction (SOD) in hypercholesterolemic rabbits following treatment with Shaoyao Gancao decoction (SGD), as well as the apoptosis of the ICC. Methods In this study, 48 healthy adult New Zealand rabbits are randomly divided into three groups (n = 16 in each group): the control, the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…This study also examined the changes of important factors within the ENS-ICCs-SMCs network, which is primarily organized by ICCs ( Gao X. et al, 2022 ). Acting as a kind of pacemaker cell, ICCs are facilitators of gastrointestinal electrical activity and regulators of neurotransmitter transmission ( Zhu et al, 2021 ). The results of this study showed that high-dose MOAE treatment significantly upregulated c-Kit in the colon and SCF in the ileum ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also examined the changes of important factors within the ENS-ICCs-SMCs network, which is primarily organized by ICCs ( Gao X. et al, 2022 ). Acting as a kind of pacemaker cell, ICCs are facilitators of gastrointestinal electrical activity and regulators of neurotransmitter transmission ( Zhu et al, 2021 ). The results of this study showed that high-dose MOAE treatment significantly upregulated c-Kit in the colon and SCF in the ileum ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ENS-ICCs-SMCs network is the basic functional unit of gastrointestinal movement, and it is mainly organized through the functions of ICCs. As a pacemaker cell for gastrointestinal activity, ICCs are also promoters of gastrointestinal electrical activity transmission and regulators of neurotransmitter transmission ( Zhu et al, 2021 ). There are a large number of neurotransmitter receptors on the cell membrane of ICCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have reported that GSP is effective in the treatment of many digestive tract disorders, few have reported the effect of GSP on GI motility. ICCs are regarded as GI pacemaker cells [12,30,31]. Abnormalities in ICCs have been implicated in GI motility disorders [12,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…ICCs are regarded as GI pacemaker cells [12,30,31]. Abnormalities in ICCs have been implicated in GI motility disorders [12,30,31]. Therefore, exploring the functions of ICCs is considered to have great significance in understanding GI motility.…”
Section: Discussionmentioning
confidence: 99%